Psychometric Properties of the Persian Version of Consideration of Future Safety Consequence (CFSC) Scale - Fazel Rajabi; Hamidreza Mokarami; Payam Farhadi; Sean Banaee; Mehdi Jahangiri (Shiraz University of Medical Sciences, 2023)
Background: Personality traits, due to having a relative stability, are important factors for predicting employees' safety behavior. Consideration of Future Safety Consequence (CFSC) is a personality trait that was recently introduced to predict the safety behaviors. The purpose of this study was to translate and assess the psychometric properties of the Persian version of the CFSC scale.Methods: In the first stage of this cross-sectional study, the instrument was prepared by the forward-backward forward translation technique and evaluated by 487 employees of a gas refinery. The validity of the scale was evaluated through face, concurrent, validity, and construct validity. The safety performance questionnaire was used to examine the concurrent validity. The reliability of the questionnaire was evaluated using internal consistency (Cronbach's alpha coefficient) and test-retest.Results: Content validity index was 0.885. The results of exploratory and confirmatory factor analysis indicated that the CFSC scale had a single factor. Also, Pearson correlation showed a positive correlation between the safety performance and the Persian version of CFSC (R=0.401). Test-retest reliability and internal consistency were calculated as 0.86 and 0.82, respectively.Conclusion: It is concluded that the psychometric properties of the Persian version of CFSC scale are desirable and can be used in future studies